POTENSI HUTAN RAWA AIR TAWAR SEBAGAI ALTERNATIF EKOWISATA BERBASIS KONSERVASI GAJAH SUMATERA (Elephas maximus sumatranus) - Rusita Rusita; Indra Gumay Febryano; Slamet Budi Yuwono; Irwan Sukri Banuwa (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2019)
Abstract. This study aims to determine the potential of fresh water swamp forest as alternative ecotourism of Sumatran elephants (Elephas maximus sumatranus). The data collection of flora was done by the printed path method, with sampling intensity (IS) 10% so that obtained 34 observation plots; then elephants behaviors were taken at 07.00 - 17.00 WIB for 7 days. The data behaviors of elephants were recorded using a sampling scan method, for 60 minutes by recording the incidence of behavior within 60 seconds. Data were analyzed by calculating the important value index, the Shannon-Wiener diversity index, and descriptif analysis. The results showed that there were 25 types of vegetation with 5 species that have the highest important index value. The diversity of vegetation types based on Shannon-Wiener's diversity index is moderate, 99% of species found are natural feeds favored by Sumatran elephants. Most of the elephant activity is eating (32%), 17% group, 17% rest, and exploring as much as 12%, while salting is done when elephants feel the need for minerals. The management can do reforestation to increase the diversity of vegetation type, especially the Sumatran elephant's natural food species, so that its existence can support the preservation of elephant and educational tourism based on Sumatran elephant conservation.